Comparison of antiplatelet effect and safety of clopidogrel napadisilate with clopidogrel bisulfate in stroke patients: multicenter, randomized, open-label, phase 4, non-inferiority clinical trial. (2nd January 2016) - Kang, Kyusik; Lee, Se-Jin; Kim, Hee-Jin; Koh, Seong-Ho; Kim, Byung Kun
Abstract: Objective: Clopidogrel napadisilate has better chemical stability than clopidogrel bisulfate. Our trial's objective was to compare the efficacy and safety of clopidogrel napadisilate with clopidogrel bisulfate in participants with ischemic stroke. Research design and methods: The study was a phase 4, 4 week, randomized, parallel-group, non-inferiority trial. Patients with ischemic stroke were randomized to receive either clopidogrel napadisilate 75 mg or clopidogrel bisulfate 75 mg. The primary study endpoint was change from baseline in P2Y12 percentage inhibition at week 4. The primary analysis was conducted in the per-protocol population. Non-inferiority was confirmed if the lower limit of the 95% confidence interval (CI) of the treatment difference was greater than or equal to −9.0% points. Results: Sixty-one participants were randomly assigned clopidogrel napadisilate and 60 were randomly assigned clopidogrel bisulfate. Thirty-nine participants in the clopidogrel napadisilate group and 39 in the clopidogrel bisulfate group were analyzed for the primary endpoint. At 4 weeks, mean P2Y12 percentage inhibition had increased in both treatment groups. The estimated mean change from baseline was 22.3% with clopidogrel napadisilate and 21.4% with clopidogrel bisulfate; the estimated treatment difference of 0.9% (95% CI, −8.6 to 10.4) confirmed the non-inferiority of clopidogrel napadisilate to clopidogrel bisulfate. Conclusions: Clopidogrel napadisilate was non-inferior to clopidogrel bisulfate as assessed by change in P2Y12 percentage inhibition. Rates of adverse events were similar between the two groups. Therefore, clopidogrel napadisilate is a useful alternative option for the dosing of ischemic stroke patient populations.